Upaya Perusahaan Otobus Antar Kota Antar Provinsi Dalam Meningkatkan Keunggulan Bersaing - Hendi Prihanto; Tamrin Lanori; Dinda Imanur Caturrahma (Universitas Kristen Maranatha, 2023)
The rise of the phenomenon of bus companies competing with each other and competing gaverise to various strategies to win their competitive advantage. For this reason, this study aimsto investigate and analyze a number of factors that cause competitiveness such as quality ofservice, technology and information systems and knowledge management on the competitiveadvantages of bus companies. The population and research sample are all bus companiesbetween cities and provinces in the island of Java, with the unit of analysis of bus companymanagers being observed in 2022 in August - December using physical and virtualquestionnaire media. Primary data analysis techniques were carried out by using statisticaldescriptive tests, testing the quality of research data instruments and other feasibility, testingthe research hypothesis, and multiple linear regression tests with SEM PLS path analysis.Findings indicate that there is a positive and significant influence on competitive advantagethrough the variables of this study, namely service quality, information technology andsystems, and knowledge management applied by bus companies. Theoretical contribution onthe theoretical aspects of detection and measurement which proves a number of variablescapable of influencing the competitive advantage of service companies. Practice/policycontribution, for company managers this research is relevant which has information andreferences in an effort to increase competitive advantage through the variables observed inthis research.Keywords: Competitive Advantage, Service Quality, Information Technology, Knowledge Management